The Effect of Decision Making and Value of Family Transaction with its Environment on Family Social Strength - Syahidah, Lutfiah; Sunarti, Euis (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Family social strength positively correlated with family transactions and its environment. This study aimed to examine decision making and the value of family transactions with its environment towards family social strength. The study used a cross-sectional design involving 120 intact families who have children under five years old and selected by stratified disproportional random sampling according to their residence (FP village and non-FP village) in Village Muara, Pasirjaya, West Bogor. The analyses showed that family social strength had a positive correlation with wife’s education level, decision making, and value of the family transaction otherwise family strength had a negatively correlated with the number of family and children. The result of the regression tests showed that decision making and the value of the family transaction had a positive effect on family social strength, but the number of children had a negative influence on family social strength. The regression tests showed either with family or without family characteristics, decision making and transaction value had a positive effect on family social strength. Contrarily, family characteristics on the number of children, both with and without the dimensions of decision making and transaction value consistently had an adverse effect on family social strength.